Anthelmintic activity of selected ethno-medicinal plant extracts on parasitic stages of Haemonchus contortus. Issue 1 (December 2016) - Kumarasingha, Rasika; Preston, Sarah; Yeo, Tiong-Chia; Lim, Diana; Tu, Chu-Lee; Palombo, Enzo; Shaw, Jillian; Gasser, Robin; Boag, Peter
Abstract Background Parasitic roundworms (nematodes) cause substantial morbidity and mortality in livestock animals globally, and considerable productivity losses to farmers. The control of these nematodes has relied largely on the use of a limited number of anthelmintics. However, resistance to many of these these anthelmintics is now widespread, and, therefore, there is a need to find new drugs to ensure sustained and effective treatment and control into the future. Methods Recently, we developed a screening assay to test natural, plant extracts with known inhibitory effects against the free-living wormCaenorhabditis elegans . Using this assay, we assessed here the effects of the extracts on motility and development of parasitic larval stages ofHaemonchus contortus, one of the most important nematodes of small ruminants worldwide. Results The study showed that two of five extracts fromPicria fel-terrae Lour. have a significant inhibitory effect (at concentrations of 3–5 mg/ml) on the motility and development ofH. contortus larvae. Although the two extracts originated from the same plant, they displayed different levels of inhibition on motility and development, which might relate to the presence of various active constituents in these extracts, or the same constituents at different concentrations in distinct parts of the plant. Conclusions These results suggest that extracts fromP. fel-terrae Lour. have promising anthelmintic activity and that more broadly, plant extracts are a potential rich source of anthelmintics to combat helminthic diseases.